Psychological morbidity in Nepali cross-border migrants in India: a community based cross-sectional study - Raja Ram Dhungana; Nirmal Aryal; Pratik Adhikary; Radheshyam Krishna KC; Pramod Raj Regmi; Bikash Devkota; Guna Nidhi Sharma; Kolitha Wickramage; Edwin van Teijlingen; Padam Simkhada (BMC, 2019)
Abstract Background Since Nepali cross-border migrants can freely enter, work and stay in India, they are largely undocumented. The majority is involved in semi-skilled or unskilled jobs with limited labour rights and social security, a fact which predisposes them to psychological distress. We aimed to assess the prevalence of and factors associated with psychological morbidity among Nepali migrants upon their return from India. Methods A community based cross-sectional study was conducted in six districts of Nepal between September 2017 and February 2018. A total of 751 participants who had worked at least six months in India and returned to Nepal were interviewed from 24 randomly selected clusters. The General Health Questionnaire (GHQ)-12 was used to measure the psychological morbidity. Data were analysed using Poisson regression analysis. Results The majority was younger than 35 years (64.1%), male (96.7%), married (81.8%), had at least a primary education (66.6%), and belonged to Dalit, Janajati and religious minorities (53.7%). The prevalence of psychological morbidity was 13.5% (CI: 11.2-16.1%). Participants aged 45 years and above (adjusted prevalence ratio (aPR) = 2.74), from the Terai (aPR = 3.29), a religious minority (aPR = 3.64), who received no sick leave (aPR = 2.4), with existing health problems (aPR = 2.0) and having difficulty in accessing health care (aPR = 1.88) were more likely than others to exhibit a psychological morbidity. Conclusion This study demonstrated that psychological morbidity was prevalent in the study participants and varied significantly with individual characteristics, work conditions and health. Multifaceted approaches including psychological counselling for returnees and protection of labour and health rights in the workplace are recommended to help reduce psychological morbidity.